Web Page Design: Implications of Memory, Structure and Scent for Information Retrieval - Larson, Kevin; Czerwinski, Mary (CHI '98 Human Factors in Computing Systems, 1998)
Much is known about depth and breadth tradeoff issues in graphical user interface menu design. We describe an experiment to see if large breadth and decreased depth is preferable, both subjectively and via performance data, while attempting to design for optimal scent throughout different structures of a website. A study is reported which modified previous procedures for investigating depth/breadth tradeoffs in content design for the web. Results showed that, while increased depth did harm search performance on the web, a medium condition of depth and breadth outperformed the broadest shallow web structure overall.